Formation and Optical Properties of Ag Nanoparticles in CaB4O7–Ag2O and CaB4O7–Gd2O3–Ag2O Tetraborate Glasses - V.T. Adamiv; Ya.V. Burak; R.V. Gamernyk; R.M. Dutka; I.M. Teslyuk (Журнал нано- та електронної фізики)
Formation of Ag nanoparticles (NPs) in the near-surface layer of CaB4O7–Ag2O and CaB4O7 –Gd2O3–Ag2O glasses by annealing in vacuum or in air is reported. It is concluded that annealing in vacuum does not necessary require the presence of reducing ions. Intensive plasmon absorption bands peaked at 403, 406 and 413.3 nm were observed in the absorption spectra of glasses with Ag NPs. Average radius of nanoparticles was calculated from the plasmon band half width and falls within 1.3-3.3 nm. It is concluded that calculated from normalized transmission spectra and absorption spectra the non-linear refractive index n2 increases due to the plasmon resonance in Ag NPs.